Development of E-Modules Using Smart Apps Creator to Improve Learning Outcomes of Islamic Cultural History Grade V - Hasbi Ibrahim; Nurdin Ibrahim; Widyasari (Indonesian Journal of Pedagogy and Teacher Education, 2024)
This study aims to develop digital teaching materials in the form of E-modules using Smart Apps Creator in learning Islamic Cultural History that are valid and effective, and can improve student learning outcomes on the material of the exemplary story of Abu Bakar Ash-Shiddiq as a friend and caliph. The development of android-based E-modules follows the Rowntree model which is integrated with the FDD (Feature Driven Development) model which has five stages of the process (Build an Overall Model, Build a Feature List Plan by Feature, Design by Feature and Build by Feature). The research subjects were material experts, instructional design experts, and learning media experts as well as MIT Salsabila students. The sample in this study was class V A. The effectiveness test was carried out by comparing the pretest and posttest scores. The results showed that the quality of the E-module developed was classified as very valid (9302%), very good in the one to one trial (93.96%) very good for small groups (94.29%) and very good for large groups (94.86%). While the t_count value is 6.4915 and the t_table value at a significant level of 5% is 2.0859 then t_count>t_table or 6.4915>2.0859, so h_a is accepted and h_0 is rejected, thus there is a significant difference in the ability between students after being given treatment in the form of using E-Modules. This shows that this E-module is feasible and effective and can facilitate students in analyzing the exemplary story of Abu Bakar Ash-Shiddiq as a friend and caliph.